Response of the bean (Phaseolus vulgaris L. CV. carioca) plant to a partially acidulated rock phosphate: I. Greenhouse studies using a red yellow latosol - Nakayama, L. J. I.; Malavolta, E. (Anais da Escola Superior de Agricultura Luiz de Queiroz, 1983)
The response of beans to a partially acidulated (50% sulfuric acid) rock phosphate (FAPS) was studied under greenhouse conditions. Simple superphosphate (SPS), the original rock phosphate (FA), and Gafsa rock phosphate (FG) were used for comparison. The soil was acidic and low in available P. Three successive crops were made to evaluate the residual effects both in presence and in absence of initial liming. Main conclusions were as following. Giving to the dry matter yield obtained with powder SPS the relative value of 100 the efficiency of the other P2O5 sources was: (1) in the absence of liming - granulate SPS = 80 FA = 85, FAPS = 75 to 90 (depending of the granule size), FG = 150; (2) in th, e presence of liming - granulate SPS = 98, FA = 66 FAPS = 70 to 85 FG = 110 Liming increase the uptake of P from all sources. FAPS served as source of Ca and S as well. After the third crop the available (01sen) P content obeyed the following decreasing order: SPS, FG, FAPS, and Fa. Respective of source the P content was lower when lime had been applied.